Influence of Different Spent Mushroom Substrates on Yield, Morphological and Photosynthetic Parameters of Strawberry (Fragaria × ananassa Duch.) - Raghavendra Prasad; Jolanta Lisiecka; Michal Antala; Anshu Rastogi (Agronomy, 2021)
The present study aimed to evaluate fresh spent mushroom substrate (SMS) as a growing medium in soilless strawberry cv. ‘Honeoye’ production. Fresh SMS after commercial production of Agaricus bisporus, Lentinus edodes, and Pleurotus ostreatus was used as a peat substitute in 15 and 25% (v/v), for strawberry cultivation in an unheated plastic tunnel. In the experiment, seven different substrates were studied, including peat (100%) as control and six substrate combinations (prepared by mixing SMSs with peat). The study was carried out in a randomized complete block design in five replicates. The results indicated that the electrical conductivity (EC), pH, and nutrient content varied among the studied substrates. The experiment also demonstrated that the substrates significantly influenced strawberry yield, leaf area, and fresh and dry plant weights. However, no significant differences were observed for selected photosynthetic parameters (Fv/Fm, Fv/F0, and PIabs) and Normalized Difference Vegetation Index (NDVI) values among the evaluated substrates. Differences were recorded for the Photochemical Reflectance Index (PRI) and Modified Chlorophyll Absorption in Reflectance Index (MCARI) values. The present investigation revealed that fresh SMSs can be an effective and inexpensive peat substitute in 15 and 25% (v/v). Therefore, such easy and immediate utilisation of SMSs could overcome associated disposal problems.